2012
DOI: 10.1007/s00233-012-9397-z
|View full text |Cite
|
Sign up to set email alerts
|

Symmetries on almost symmetric numerical semigroups

Abstract: The notion of almost symmetric numerical semigroup was given by V. Barucci and R. Fröberg in [BF]. We characterize almost symmetric numerical semigroups by symmetry of pseudo-Frobenius numbers. We give a criterion for H * (the dual of M ) to be almost symmetric numerical semigroup. Using these results we give a formula for multiplicity of an opened modular numerical semigroups. Finally, we show that if H 1 or H 2 is not symmetric, then the gluing of H 1 and H 2 is not almost symmetric.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
45
0
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 9 publications
(2 reference statements)
1
45
0
5
Order By: Relevance
“…In other words, one has the following result: The type of a numerical semigroup C is defined in [11] as the number of elements in the set C ′ = {x ∈ Z/ x / ∈ C and x + s ∈ C , ∀s ∈ C \ {0}}. In [15,Prop. 6.6] it is shown that the type of a numerical semigroup obtained by gluing two semigroups is the product of the types of the two semigroups.…”
Section: Main Results and Consequencesmentioning
confidence: 99%
“…In other words, one has the following result: The type of a numerical semigroup C is defined in [11] as the number of elements in the set C ′ = {x ∈ Z/ x / ∈ C and x + s ∈ C , ∀s ∈ C \ {0}}. In [15,Prop. 6.6] it is shown that the type of a numerical semigroup obtained by gluing two semigroups is the product of the types of the two semigroups.…”
Section: Main Results and Consequencesmentioning
confidence: 99%
“…It is known by Nari [27] that K [H] is almost Gorenstein, if and only if (10) f The following result shows that a numerical semigroup generated by an arithmetic sequence is nearly Gorenstein. We also characterize when such semigroups are almost symmetric, taking into account that the symmetric case was known from work of Gimenez, Sengupta and Srinivasan in [13].…”
mentioning
confidence: 99%
“…Unfortunately there exist almost symmetric numerical semigroups with odd type that cannot be constructed in this way. For example consider T = 9, 10, 14, 15 = {0, 9,10,14,15,18,19,20 in any case E is not contained in S and then E is not a proper ideal of S.…”
Section: One Half Of Almost Symmetric Numerical Semigroups With Odd Typementioning
confidence: 99%